PENGARUH HIPERTENSI LEARNING TERHADAP TINGKAT KECEMASAN PASIEN HIPERTENSI DI RUMAH SAKIT X - Septiani, Yuliya; Susanto, Wigyo; Rochmawati, Dwi Heppy (Journal Healthcare Education, 2026)
The development of digital technology in the health sector has given birth to various health learning applications, one of which is a special education application for hypertension. This study aims to determine the effect of hypertension learning on anxiety levels in hypertension patients at Sari Asih Hospital, Serang. Method: This study uses a quantitative approach with a pretest & posttest design, using a total sampling technique. Hypothesis testing uses a marginal homogeneity test. The questionnaire uses the Zung Self Anxiety Scale. Results: The P Value is: 0.157 which is greater than 0.05 (>0.05), which means there is no significant difference between anxiety levels before and after the intervention. The correlation coefficient (r) cannot be calculated because all anxiety values ​​in the post-test are in one category, namely all mild (there is no data variation). The direction of the relationship is positive, because it is towards improvement in all (towards mild), the density of the relationship is clinically strong, because 100% of the post-test results are in the best category (mild). Conclusion: Although no statistically significant differences were found, the Hypertension Learning application was clinically effective in maintaining and improving anxiety levels in hypertensive patients. These findings support the theory that digital education increases self-efficacy, reduces perceived threat of illness, and improves psychological responses in chronic patients. Therefore, Hypertension Learning continues to have important practical and clinical value as part of technology-based nursing interventions in the era of digital transformation in healthcare.